2009
DOI: 10.1088/0029-5515/49/6/062003
|View full text |Cite
|
Sign up to set email alerts
|

H-mode threshold and confinement in helium and deuterium in ASDEX Upgrade

Abstract: In 2008, experiments have been carried out in ASDEX Upgrade to compare Hmode power threshold and confinement time in helium and deuterium. A scan in magnetic field and a wide density variation indicate that the threshold power in the two gases is very similar. The density dependence of the threshold exhibits a clear minimum. Confinement in helium is about 30% lower than in deuterium, mainly due to the reduction of the ion density caused by Z=2 in helium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
141
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(174 citation statements)
references
References 13 publications
(27 reference statements)
31
141
2
Order By: Relevance
“…They revealed that the threshold was about 25% lower than previous data and therefore also below the scaling by the same amount, [14]. This has been confirmed during the following campaigns 2011-2013.…”
Section: Transition From Graphite To Tungsten Wallsupporting
confidence: 66%
See 1 more Smart Citation
“…They revealed that the threshold was about 25% lower than previous data and therefore also below the scaling by the same amount, [14]. This has been confirmed during the following campaigns 2011-2013.…”
Section: Transition From Graphite To Tungsten Wallsupporting
confidence: 66%
“…[1] and references therein, and has been the subject of recent studies [45,14,46]. The threshold exhibits a minimum atn e,min which separates the so-called low and high density branches.…”
Section: L-h and H-l Power Thresholdsmentioning
confidence: 99%
“…Multiplying these values by the minor radius gives an apparent poloidal rotation velocity of 1.4 km s −1 . 17 Sets of filaments regularly appear within a short time interval as shown in figure 17(b). Here, the average mapping target angles at the time of the highest intensity for the four most intense structures are highlighted by dashed lines.…”
Section: Correlation Of Smps To Elm Filamentsmentioning
confidence: 96%
“…While increasing (decreasing) the input power in this discharge the ELM frequency increases (decreases). In addition, during the investigated phase the discharge is heated with 7.5 MW by neutral beam injection, which is significantly further above the typical LH threshold for the parameters of this discharge (P LH ∼ 1.6 MW [17]). This is also higher than the range, in which type III ELMs are usually observed.…”
Section: Quantification and Scaling Of Solitarinessmentioning
confidence: 98%
“…One rationale for this case is that it could be important for obtaining H-mode in the pre-activation phase, especially if the H-mode cannot be achieved in bulk hydrogen. Scalings for the L→H power threshold in He 4 plasmas are controversial, but some tokamaks report lower H-mode threshold in He 4 than in H [11]. The predictions achieve H-mode with extrapolations of database results for P LH [12].…”
Section: Benchmark Casesmentioning
confidence: 79%